2016
DOI: 10.1007/s40725-016-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Evolutionary Potential of Tree Populations to Cope with Newly Introduced Pests and Pathogens—Lessons Learned From Forest Health Catastrophes in Recent Decades

Abstract: Emerging diseases often originate from host shifts of introduced pests or pathogens. Genetic resistance of the host to such diseases might be limited or absent due to the lack of coevolutionary history. We review six examples of major disease outbreaks on native tree species caused by different introduced pests and pathogens that led to large ecological and economical losses. In all six cases, high tree mortality was observed in natural populations with some surviving individuals exhibiting varying levels of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 124 publications
(126 reference statements)
0
39
0
Order By: Relevance
“…It is still unknown if this is also the case for North American ashes. When facing a potential new pathogen, as broad a genetic base as possible should be deployed in the planted areas to improve the resilience of the plantings (Budde et al 2016).…”
Section: Future Prospects In Europe and North Americamentioning
confidence: 99%
“…It is still unknown if this is also the case for North American ashes. When facing a potential new pathogen, as broad a genetic base as possible should be deployed in the planted areas to improve the resilience of the plantings (Budde et al 2016).…”
Section: Future Prospects In Europe and North Americamentioning
confidence: 99%
“…Moderate clonal repeatability values were obtained in both field and laboratory conditions, as reported in similar studies of disease response in mapping populations of forest trees: 0.54–0.94 for the poplar– Melampsora larici‐populina pathosystem in both controlled and natural conditions (Jorge et al , ), 0.59 for the Eucalyptus globulus – Mycosphaerella cryptica interaction in natural conditions (Freeman et al ., ), and 0.36–0.92 for various strains of Melampsora larici‐epitea on willow hybrids (Samils et al ., ). Heritability estimates were in the range expected for disease resistance in trees (Carson & Carson, ), including those observed in noncoevolved pathosystems (Budde et al ., ). However, heritability values depend on many factors, including the genetic variability of the host population tested, age at assessment, environmental conditions, and screening methods.…”
Section: Discussionmentioning
confidence: 97%
“…In a context of increasing forest damage due to emerging diseases world‐wide (Liebhold et al , ; Santini et al ., ), improving our understanding of the genetic basis of tree resistance to pathogens is a priority research topic. Genetic variation in susceptibility to pathogens will condition the ability of populations to evolve resistance, either in nature or through breeding programs (Ennos, ; Budde et al ., ). Interestingly, the recent sequencing of the oak ( Quercus robur ) genome suggested that the expansion of disease‐related gene families could be an important genomic feature associated with long lifespan in trees (Plomion et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Pitch canker was only recognized in California in 1986 (McCain, Koehler, & Tjosvold, 1987), and it appears to have been an introduction from the south-eastern United States (Wikler & Gordon, 2000), with no evidence that geographic ranges of host and pathogen overlapped prior to that. In the absence of selection pressure for resistance to pitch canker in P. radiata, variation in susceptibility may be attributable to a reservoir of neutral variation (Budde et al, 2016;Petit & Hampe, 2006), which is seen as integral to the capacity of tree species to respond effectively to challenges posed by exotic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The vast extent of forested land, which presently covers approximately 27% of the terrestrial surface of the earth (Petit & Hampe, 2006), suggests that tree populations have the capacity to respond effectively to exotic pathogens. This capacity has been attributed to a deep reservoir of genetic diversity in the form of large populations and extensive gene flow (Budde, Nielsen, Ravn, & Kjaer, 2016).…”
Section: Introductionmentioning
confidence: 99%